2007
DOI: 10.1097/01.sla.0000264507.79859.f9
|View full text |Cite
|
Sign up to set email alerts
|

Stored Packed Red Blood Cell Transfusion Up-regulates Inflammatory Gene Expression in Circulating Leukocytes

Abstract: PRBCs activate inflammatory genes in circulating leukocytes, which may be central to the pathogenesis of the adverse inflammatory responses that lead to postinjury MOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 35 publications
0
40
0
5
Order By: Relevance
“…These reactions include elevated level of mediators such as IL-6 or IL-10 [15] and increased leukocyte activation (reviewed in [16]). Additional experiments revealed that the expression of inflammatory genes in leukocytes is enhanced after incubation with packed RBCs ex vivo in vitro [17]. In the present work, it was demonstrated that dendritic cells are also somehow affected.…”
Section: And Pdc In Dependency Of the Injury Patternmentioning
confidence: 81%
“…These reactions include elevated level of mediators such as IL-6 or IL-10 [15] and increased leukocyte activation (reviewed in [16]). Additional experiments revealed that the expression of inflammatory genes in leukocytes is enhanced after incubation with packed RBCs ex vivo in vitro [17]. In the present work, it was demonstrated that dendritic cells are also somehow affected.…”
Section: And Pdc In Dependency Of the Injury Patternmentioning
confidence: 81%
“…Transfusion is a potent stimulus for inflammatory gene expression after trauma (73,74). The administration of fresh-frozen plasma has also been linked to ARDS and an increased risk of organ dysfunction (75).…”
Section: Other Iatrogenic Determinants Of the State Of Critical Illnessmentioning
confidence: 99%
“…Other possible mechanisms for the contribution of transfusion to ischemic complications include pro-inflammatory effects, for example by activation of inflammatory genes (such as upregulation of IL-8 and Toll-like receptor 4 or circulating leukocytes [41]), as well as storage defects. In this context, leukocytes have also been reported to accelerate the rate of storage lesions [42].…”
Section: Impact Of Storage Time On Quality Of Red Blood Cell Unitsmentioning
confidence: 99%